2022
DOI: 10.1002/micr.30997
|View full text |Cite
|
Sign up to set email alerts
|

The combined profunda artery perforator‐gracilis flap for immediate facial reanimation and resurfacing of the radical parotidectomy defect

Abstract: Background A radical parotidectomy with facial nerve sacrifice results in facial nerve paralysis as well as a volume and often cutaneous defect. Prior experience with nerve grafting and static suspension has yielded suboptimal results. The present report aims to examine the feasibility and outcomes of a combined free gracilis and profunda artery perforator (PAP) flap from a single donor site can reconstruct these extensive defects and potentially restore dynamic facial reanimation even in the setting of adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Clinical utility of this flap has been demonstrated by both Heredero et al 3 and Yao et al 4 in large-volume head and neck reconstruction. 3,4 Despite the utility of the combined flap, the identification, dissection, and microsurgical anastomosis (if used as a free flap) of two distinct pedicles represents a significant disadvantage of prolonged operative time, greater risk of anastomotic complications, and resources. As we have previously demonstrated feasibility of a chimeric flap harvest in cadaveric models 2 , pre-operative mapping through CTA could allow for identification of a common arterial pedicle and improve pre-operative planning and resource utilization.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Clinical utility of this flap has been demonstrated by both Heredero et al 3 and Yao et al 4 in large-volume head and neck reconstruction. 3,4 Despite the utility of the combined flap, the identification, dissection, and microsurgical anastomosis (if used as a free flap) of two distinct pedicles represents a significant disadvantage of prolonged operative time, greater risk of anastomotic complications, and resources. As we have previously demonstrated feasibility of a chimeric flap harvest in cadaveric models 2 , pre-operative mapping through CTA could allow for identification of a common arterial pedicle and improve pre-operative planning and resource utilization.…”
Section: Introductionmentioning
confidence: 95%
“…1,2 Due to its chimeric design, this flap may potentially offer greater soft tissue volume than either a singular gracilis or PAP flap, providing flexibility for reconstruction, especially in scenarios featuring a large defect. Clinical utility of this flap has been demonstrated by both Heredero et al 3 and Yao et al 4 in large-volume head and neck reconstruction as well as in perineal reconstruction. [5][6][7] Despite the utility of the combined flap, the identification, dissection, and microsurgical anastomosis (if used as a free flap) of two distinct pedicles represents a significant disadvantage of prolonged operative time, greater risk of anastomotic complications, and resources.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The perforator anatomy again has proven to be remarkably reliable and likely more reliable than the ALT, which can have tremendous variation and in some circumstances may not have any suitable perforators at all. For many head and neck patients who suffer from weight loss due to the extensive tumor burden, pain, trismus, or the sequelae of previous radiation, the PAP can provide tissue that is thicker than the ALT ( Figure 5 and Figure 6 ) [ 24 , 25 , 26 ]. The length of the flap can be tailored to the size of the defect, but the width that can be harvested is variable from patient to patient and is dependent on the laxity in the donor site.…”
Section: Profunda Artery Perforator Flapmentioning
confidence: 99%
“…While these factors were considered relative contraindications to dynamic reconstruction in the past, we have confirmed that patients undergoing immediate functional gracilis transfer were able to achieve volitional control. When using a single donor site from the medial thigh, a profunda artery perforator (PAP) flap can be harvested with the gracilis muscle allowing the reconstructive microsurgeon to address the volume deficit using the PAP flap and restore dynamic facial movement using the gracilis muscle [ 66 ]. A simultaneous harvest of the PAP and gracilis can be performed in the supine position.…”
Section: Facial Reanimationmentioning
confidence: 99%